Decreased Bone Mineral Density at the Femoral Neck and Lumbar Spine in South Indian Patients with Type 2 Diabetes - Pratheesh George Mathen; Molly Mary Thabah; Bobby Zachariah; Ashok Kumar Das (Journal of Clinical and Diagnostic Research, 2015)
Background: With prevalence of diabetes in India reaching epidemic proportions and increase in the population of geriatric age group and risks of falls, it is important to understand the effect that diabetes has on bone health. Aim: The objective was to assess bone mineral density (BMD) of patients with type 2 diabetes mellitus (T2DM) and to study factors contributing to BMD in patients with T2DM. Materials and Methods: This was a prospective crosssectional study on 150 patients with T2DM (diagnosed at age > 30 years) and an equal number (n=150) of age and sex matched healthy controls from September 2012 to July 2014 at a tertiary care center located in Southern India. BMD was measured at the femoral neck and lumbar spine (L2–L4) by dual energy absorptiometry (DXA) in cases and controls. Serum total calcium, phosphorus and alkaline phosphatase (ALP) and 25- OH- vitamin D3 was measured in patient group. Results: Mean age (SD) was 51.29 (±8.05) and 51 (±8.3) years in cases and controls, respectively. The femoral neck and lumbar spine BMD was significantly lower in T2DM cases compared to controls. Also the femoral neck and lumbar spine T-score was significantly lower in T2DM cases compared to controls. Femoral neck BMD among male patients with T2DM was significantly lower compared to controls (men). Among women, BMD at femoral neck as well as lumbar spine was significantly lower in cases when compared to controls. Ninety six out of 150 (64%) T2DM cases had Vitamin D values <20 ng/mL. There was weak negative correlation between age of patient, duration of diabetes and HbA1C with femoral neck BMD. There was weak negative correlation between HbA1C and lumbar spine BMD. Conclusion: Indian subjects with type 2 diabetes have significantly lower BMD at both femoral neck and lumbar spine compared to age and sex matched healthy controls. We conclude that osteopenia and osteoporosis are overlooked complications of diabetes. Longitudinal studies are needed to see for actual incidence of fractures among this high risk group.